Enhancing Generation Z's Engagement in Social Movements through Social Media-Based Education - José Taçain (Mandalika: Jurnal Ilmu Pendidikan dan Bahasa, 2026)
This study explores the potential of social media-based education in enhancing Generation Z's engagement in social movements. Using a qualitative research design and a literature review methodology, the study synthesizes findings from various scholarly articles to understand the intersection between social media, youth activism, and education. The results show that while social media platforms are powerful tools for raising awareness and initiating engagement, they often fail to translate digital participation into tangible offline action. The literature suggests that social media-based education can bridge this gap by fostering critical thinking, equipping youth with the necessary tools to engage in social issues, and aligning educational content with the values of Generation Z. However, challenges remain in ensuring that online participation leads to sustained, meaningful activism. The study proposes integrating interactive and participatory educational models within social media platforms to encourage deeper engagement, shifting young people from passive digital participation to active real-world involvement. This approach has significant implications for the field of youth activism and social media-based education, highlighting the importance of creating educational interventions that not only inform but also inspire Generation Z to take action and contribute to societal change. The findings contribute to the growing body of knowledge on how social media can be leveraged for educational purposes and youth activism. Further research is needed to explore the long-term impact of social media-based education on youth activism and to examine the effectiveness of specific platforms and content in promoting sustained social change.